The Role of Tahfidz Al-Quran Learning in Assisting Religious Studies - Susanto Susanto; Muhammad Ali Muhaidori (Yayasan Adra Karima Hubbi, 2024)
Background. Islamic religious learning in schools generally focuses on the discussion of Qur'anic verses. However, many students have difficulty in reading the Qur'an correctly and precisely, even more so in memorizing these verses. This raises questions about the effectiveness of existing learning methods and the potential role of learning tahfidz Al-Qur'an in helping religious lessons. Purpose. This study aims to determine the role of learning tahfidz Al-Qur'an in helping religious lessons, especially in the context of learning Al-Qur'an Hadith. Method. The research uses a qualitative descriptive method. Sampling was carried out by the purposive method, with the key informants being class teachers and students of SDIT Nurul 'Ilmi Tenggarong. Data collection techniques include observation, interviews, and documentation. Results. The results of the study show that the learning of tahfidz Al-Qur'an has a very important position in helping religious learning, especially the learning of the Qur'an Hadith. Al-Qur'an tahfidz activities have a positive influence on students' learning of the Qur'an Hadith. Students who are diligent in reading and memorizing the Qur'an tend to have better learning activity. Conclusion. Learning tahfidz Al-Qur'an plays an important role in improving students' abilities in learning Al-Qur'an Hadith. Discipline in reading and memorizing the Qur'an is positively correlated with learning discipline, which ultimately improves the learning outcomes of the Qur'an Hadith subject. This research highlights the importance of integrating tahfidz Al-Qur'an learning in the Islamic religious education curriculum to improve students' understanding and skills in understanding and practicing Islamic teachings.